Developing an Accreditation Intelligence Dashboard as a Decision Support System for Continuous KARS Compliance in Hospitals - Diah Karlina (Journal of Innovative and Creativity, 2026)
Background:Hospital accreditation is a key mechanism for ensuring quality and patient safety, yet in many hospitals accreditation compliance remains episodic and weakly embedded in routine governance. In Indonesia, compliance with the Hospital Accreditation Commission (KARS) standards is often managed retrospectively, limiting the role of accreditation as a continuous quality improvement instrument. Digital decision-support approaches are therefore needed to strengthen continuous accreditation governance. Methods:This study employed a mixed-methods design with a design science research approach in a private general hospital in Indonesia. Data were collected through document analysis of KARS standards and hospital performance reports, semi-structured interviews with hospital managers and accreditation team members, and non-participant observation of accreditation-related workflows. Qualitative data were analyzed thematically, while accreditation indicators were systematically mapped to existing hospital information systems to inform the development of an Accreditation Intelligence Dashboard. Results:The findings indicate that although accreditation-related data are widely available, they are fragmented across multiple systems and primarily used for survey preparation rather than continuous monitoring. The proposed Accreditation Intelligence Dashboard integrates key KARS indicators with operational hospital data using a business intelligence framework. This integration enables real-time visualization, trend analysis, and managerial decision support, enhancing situational awareness and internal accountability. The effectiveness of the dashboard is influenced by leadership engagement and organizational readiness for data-driven management. Conclusion:The study demonstrates that an Accreditation Intelligence Dashboard can support continuous KARS compliance by transforming fragmented accreditation data into actionable managerial intelligence. This approach strengthens hospital quality governance and has potential to support the quality objectives of Universal Health Coverage.